Human Adipose-Derived Mesenchymal Stem Cells for Osseous Rehabilitation of Induced Osteoradionecrosis: A Rodent Model - Janus, Jeffrey R; Jackson, Ryan S; Lees, Katherine A; Voss, Stephen G; Wilson, Zachary C; Remmes, Nicholas B; Keeney, Michael G; Garcia, Joaquin J; San Marina, Serban (Otolaryngology-head and neck surgery, 2017)
Objective Human adipose-derived mesenchymal stem cells (ADSCs) were used to rehabilitate bone damaged by osteoradionecrosis (ORN) in an established animal model. Study Design Prospective animal study. Setting Academic department laboratory. Subjects and Methods After institutional review board and Institutional Animal Care and Use Committee approval, 24 athymic nude rats were divided into 5 groups: 4 groups irradiated (20 Gy) by brachytherapy catheter placed at the left hemimandible and 1 mock irradiation control (n = 4). For all groups, ORN was initiated by extraction of the central molar 1 week later. After 28 days, animals (n = 5/group) received injection at the extraction site with saline (SAL), ADSCs, platelet-rich plasma and collagen (PRP/COL), or ADSCs + PRP/COL. Rats were sacrificed 28 days later and their mandibles harvested for histopathology analysis (osteoblasts, osteoclasts, and fibrosis) and bone volume measurement using 3-dimensional micro-computed tomography. Results All but 1 rat survived the experiment period (23/24). Radiographic and histological analysis revealed 60% bone loss in the SAL group compared with the nonirradiated control. Injection of ADSCs increased jaw region bone volume by up to 36% ( P < .01). All experimental groups (ADSC, PRP/COL, and ADSC + PRP/COL) showed dramatically decreased osteoclast counts ( P < .001) while injection of PRP/COL with or without ADSCs increased osteoblasts. Increased fibrosis was observed after ADSC injection ( P < .05). Conclusion The application of human ADSCs to an induced mandibular osteoradionecrosis model in athymic rats results in increased deposition or preservation of bone, demonstrated both histologically and radiographically. This offers an encouraging possible treatment option for translational research in this difficult disease.